Investigation of Thermal Stability of P2-NaxCoO2 Cathode Materials for Sodium Ion Batteries Using Real-Time Electron Microscopy - Hwang, Sooyeon; Lee, Yongho; Jo, Eunmi; Chung, Kyung Yoon; Choi, Wonchang; Kim, Seung Min; Chang, Wonyoung (American Chemical Society, 2017)
Here, we take advantage of in situ transmission electron microscopy (TEM) to investigate the thermal stability of P2-type NaxCoO2 cathode materials for sodium ion batteries, which are promising candidates for next-generation lithium ion batteries. A double-tilt TEM heating holder was used to directly characterize the changes in the morphology and the crystallographic and electronic structures of the materials with increase in temperature. The electron diffraction, patterns and the electron energy loss spectra demonstrated the presence of cobalt oxides (Co3O4), CoO) and even metallic cobalt,(Co) at higher temperatures as a result of reduction of Co ions and loss of oxygen. The bright-field TEM images revealed that the surface of NaxCoO2, becomes porous at high temperatures. Higher, cutoff voltages result in degrading thermal stability of NaxCoO2. The observations herein provide a valuable insight that thermal stability is one of the important factors to be considered in addition to the electrochemical properties when developing, new electrode materials for novel battery systems.
Keywords: SPECTROSCOPY; NACRO2; CHARGE